Integrated prevalence mapping of schistosomiasis, soil-transmitted helminthiasis and malaria in lakeside and island communities in Lake Victoria, Uganda - Kabatereine Narcis B; Standley Claire J; Sousa-Figueiredo Jose C; Fleming Fiona M; Stothard J Russell; Talisuna Ambrose; Fenwick Alan (Parasites & Vectors, 2011)
Abstract Background It is widely advocated that integrated strategies for the control of neglected tropical diseases (NTDs) are cost-effective in comparison to vertical disease-specific programmes. A prerequisite for implementation of control interventions is the availability of baseline data of prevalence, including the population at risk and disease overlap. Despite extensive literature on the distribution of schistosomiasis on the mainland in Uganda, there has been a knowledge gap for the prevalence of co-infections with malaria, particularly for island communities in Lake Victoria. In this study, nine lakeshore and island districts were surveyed for the prevalence of NTDs and malaria, as well as educational and health infrastructure. Results A total of 203 communities were surveyed, including over 5000 school-age children. Varying levels of existing health infrastructure were observed between districts, with only Jinja District regularly treating people for NTDs. Community medicine distributors (CMD) were identified and trained in drug delivery to strengthen capacity. Prevalence levels of intestinal schistosomiasis and soil-transmitted helminthiasis were assessed via Kato-Katz thick smears of stool and malaria prevalence determined by microscopy of fingerprick blood samples. Prevalence levels were 40.8%, 26.04% and 46.4%, respectively, while the prevalence of co-infection by Schistosoma mansoni and Plasmodium spp. was 23.5%. Socio-economic status was strongly associated as a risk factor for positive infection status with one or more of these diseases. Conclusions These results emphasise the challenges of providing wide-scale coverage of health infrastructure and drug distribution in remote lakeshore communities. The data further indicate that co-infections with malaria and NTDs are common, implying that integrated interventions for NTDs and malaria are likely to maximize cost-effectiveness and sustainability of disease control efforts.